Reaction path modelling of in-situ mineralisation of CO2 at the CarbFix site at Hellisheidi, SW-Iceland - Snæbjörnsdóttir, S; Gislason, SR; Galeczka, IM; Oelkers, EH (2018)
Results from injection of 175 tonnes of CO 2 into the basaltic subsurface rocks at the CarbFix site in SW-Iceland in 2012 show almost complete mineralisation of the injected carbon in less than two years (Matter et al., 2016; Snæbjörnsdóttir et al., 2017). Reaction path modelling was performed to illuminate the rate and extent of CO 2 -water-rock reactions during and after the injection. The modelling calculations were constrained by the compositions of fluids sampled prior to, during, and after the injection, as reported by Alfredsson et al. (2013) and Snæbjörnsdóttir et al. (2017). The pH of the injected fluid, prior to CO 2 dissolution was ∼9.5, whereas the pH of the background waters in the first monitoring well prior to the injections was ∼9.4. The pH of the sampled fluids used in the modelling ranged from ∼3.7 at the injection well to as high as 8.2 in the first monitoring well. Modelling results suggest that CO 2 -rich water-basalt interaction is dominated by crystalline basalt dissolution along a faster, high permeability flow path, but by basaltic glass dissolution along a slower, pervasive flow path through which the bulk of the injected fluid flows. Dissolution of pre-existing calcite at the onset of the injection does not have a net effect on the carbonation, but does contribute to a rapid early pH rise during the injection, and influences which carbonate minerals precipitate. At low pH, Mg, and Fe are preferentially released from crystalline basalts due to the higher dissolution rates of olivine, and to lesser extent pyroxene, compared to plagioclase and glass (Gudbrandsson et al., 2011). This favours the formation of siderite and Fe-Mg carbonates over calcite during early mineralisation. The model suggests the formation of the following carbonate mineral sequences: siderite at pH < 5, Mg-Fe-carbonates and Ca-Mg-Fe-carbonates at pH > 5, and calcite at higher pH. Other minerals forming with the carbonates are Al- and Fe-hydroxides and chalcedony, and zeolites and smectites at elevated pH. The ...